On the approximation of the spectral expansions of distributions in the weak topology - Rakhimov, Abdumalik A. (INSInet Publications, 2012)
In this paper we study approximations of distributions on a smooth manifold. We obtain sufficient conditions of summation of the series in the weak topology. As applications we consider spectral expansions connected with elliptic partial differential operators.